Effect of Die Radius on Blank Holder Force and Drawing Ratio: A Model and Experimental Investigation - Sezek, S.; Savas, V.; Aksakal, B. (Taylor & Francis Inc, 2010)
A numerical model for a newly designed deep drawing process has been built up and analyzed using the finite element method (FEM) in comparison with performed experiments using the DIN 10130-99-DC05 sheet material. It was aimed to increase the limiting drawing ratio () and decrease the blank holder forces (BHFs). To predict the deformation behavior of the process, the parameters are analyzed using FEM. The effects of the die radius, blank holder and punch forces, friction, cup wall, and blank thickness in the process were investigated. A deep drawing die set was designed and manufactured, and the validity of the design was demonstrated through the theoretical and experimental analysis. The results showed that the blank holder die radii and friction have the greatest effect on the thickness of deformed steel cups. The drawing ratio of has an influence on the BHFs and it decreased with increasing die angle (). The was considerably increased by 26% compared with dies having no angle (=0 degrees). The current design and analyses can help the optimization of the control scheme of drawing processes rather than using the conventional designs. A comparison of the predicted and experimental results showed good agreement.
Keywords: BHF; Deep drawing; Metal forming BHF